EFEKTIVITAS PENGGUNAAN MICROSOFT TEAMS SAAT WFH DI PT. BALI ANIMASI SOLUSI EKAKARSA - Prayoga, I Made Rai; Mandira, I Made Chandra (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2021)
Companies can develop not only depending on the quality of their human resources, but in times like today, modern equipment and complete infrastructure have become important aspects of the company. The Corona Virus or Covid-19 which has infected the whole world at this time has caused many companies that require large amounts of human resources to experience a decrease in production effectiveness due to various limitations faced. One of the affected companies is PT. Bali Animation Solutions Ekakarsa or better known as Brown Bag Films bali. The policy taken by the company to remain productive is WFH (Work From Home) or working from home to help the government in suppressing the spread of this virus and being able to remain productive during a pandemic like today. Companies are required to be able to rely on all types of existing technology media, it aims to facilitate the work of employees. One online application that can help with this is Microsoft Teams. Microsoft Teams is an online application created by Microsoft based on full-featured chat with support for document sharing, online meetings and other features that are very useful for companies to communicate. The use of Microsoft Teams can be an answer to the various limitations that companies are currently experiencing, so that limitations do not become a barrier to staying productive even during a pandemic. Keywords: Covid-19, WFH (Work From Home), Microsoft Teams